Ulinastatin Protects Against LPS-Induced Acute Lung Injury By Attenuating TLR4/NF-κB Pathway Activation and Reducing Inflammatory Mediators. Issue 5 (November 2018) - Cao, Chao; Yin, Chengfen; Shou, Songtao; Wang, Jun; Yu, Lechang; Li, Xuening; Chai, Yanfen
Abstract : ABSTRACT: Acute lung injury (ALI) and its severe form, acute respiratory distress syndrome, remain the leading causes of morbidity and mortality in intensive care units. Ulinastatin (UTI), a serine protease inhibitor, possesses anti-inflammatory properties and has been suggested to modulate lipopolysaccharide (LPS)-induced sepsis; thus, it is now widely used in the treatment of pancreatitis, sepsis, and septic shock. Toll-like receptor 4 (TLR4), an essential LPS signaling receptor, plays a critical role in the activation of innate immunity. The aim of this study was to investigate whether UTI alleviates ALI by attenuating TLR4 expression and to explore the underlying molecular mechanisms involved. Male C56BL/6 mice were administered UTI intravenously 1 h before and 6 h after exposure to LPS by intratracheal instillation. Human lung epithelial (BEAS-2B) cells were incubated with LPS in the presence or absence of UTI. An enzyme-linked immunosorbent assay was used to detect levels of inflammatory cytokines. Western blot analysis was performed to detect changes in TLR4 expression and nuclear factor-κB (NF-κB) activation. UTI significantly protected animals from LPS-induced ALI, decreasing the lung wet/dry weight ratio, ALI score, total cells, neutrophils, macrophages, myeloperoxidase activity, and malondialdehyde content, factors associated with lung histological damage. UTI treatment also markedly attenuated levels of TLR4 and other proinflammatory cytokines. Furthermore, UTI significantly attenuated LPS-induced increases in TLR4 protein expression and NF-κB activation in lung tissues. Similarly, UTI markedly attenuated TLR4 expression and NF-κB activation in LPS-stimulated BEAS-2B cells. These findings indicate that UTI ameliorates LPS-induced ALI by attenuating the TLR4/NF-κB pathway activation.